2008
DOI: 10.1080/10717540802327047
|View full text |Cite
|
Sign up to set email alerts
|

Transdermal Delivery of Carvedilol Containing Glycyrrhizin and Chitosan as Permeation Enhancers: Biochemical, Biophysical, Microscopic and Pharmacodynamic Evaluation

Abstract: The present study was aimed at unveiling the influence of glycyrrhizin and chitosan on rat epidermis and to correlate these effects with percutaneous permeation characteristics of carvedilol. The permeation of carvedilol across excised rat epidermis was significantly higher ( p < 0.05) when glycyrrhizin, chitosan, or glycyrrhizin-chitosan mixture was used as a donor vehicle as compared to propylene glycol:ethanol (7:3) mixture. Epidermis obtained after 12 hr treatment of viable rat skin with a glycyrrhizin-chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 25 publications
(19 reference statements)
1
21
0
Order By: Relevance
“…The effect of GA and chitosan on the transdermal delivery of carvediol was also studied (Sapra et al, 2008). It has been found that the solubility of carvediol in solution containing 0.75% GA increases by a factor of 59 compared to the buffer solution.…”
Section: Self-association Of Ga and Its Use In Drug Deliverymentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of GA and chitosan on the transdermal delivery of carvediol was also studied (Sapra et al, 2008). It has been found that the solubility of carvediol in solution containing 0.75% GA increases by a factor of 59 compared to the buffer solution.…”
Section: Self-association Of Ga and Its Use In Drug Deliverymentioning
confidence: 99%
“…It provides broad prospects of applying of glycyrrhizic acid as a multifunctional DDS. It was also established that GA enhance absorption effects of the variety of drugs (Kong et al, 2017;Sapra et al, 2008;Radwant and Aboul-Enein, 2002;Chen et al, 2009;Chakotiya et al, 2016). In view of the fact that the movement of small drug molecules through gastrointestinal epithelium is regulated by the distension and constriction of the tight junctions, observed effects could be connected with the ability of glycyrrhizin to enhance the penetration of molecules into the cells.…”
Section: Permeability Enhancement and Membrane-modifying Activitymentioning
confidence: 99%
“…GA has been reported to have an influence on drug permeation in the skin (Sapra et al, 2008), and it has also been studied as a paclitaxel micelle carrier in our research group (Yang et al, 2015). In the present study, GA's solubilization property improved the solubility of POD and the formulation could reach a concentration of 5 mg/mL.…”
Section: Discussionmentioning
confidence: 53%
“…Permeation enhancement effect of chitosan has been reported by Sapra et al (2008) in the transdermal delivery of carvedilol.…”
Section: Chitosan and Its Derivativesmentioning
confidence: 99%